基于面心组合的排气歧管响应曲面优化设计 - 刘伟; 张勇; 程天才; 王海燕 (Jixie qiangdu)
In order to solve the limitations caused by the engine exhaust manifold structure optimization which usually adopts single factor control variable method or orthogonal test leading to the insignificant parameter interaction,the face centered combination method in the central composite design is used to respond to surface optimization,taking the engine exhaust manifold of a heavy chemical vehicle as the research object,the exhaust 38 groups of manifold structural parameters finish the fast matching,the mathematical model is established and polynomial response regression equation is concluded,fitting out of the exhaust manifold optimum structural parameters and corresponding flow uniformity index,additionally,the results of response surface optimization is verified by the numerical simulation.The results show that when the four branches are combined,the optimal structure fluid flow uniformity index of the exhaust manifold by the response surface method based on the face centered combination way is improved from the original 0.76 to 0.82,which is 6% higher than the initial structure.